Predictors of Metachronous Risk Polyps After Index Colonoscopy. Issue 2 (18th February 2021) - Carot, Laura; Navarro, Gemma; Naranjo-Hans, Dolores; Iglesias-Coma, Mar; Dalmases, Alba; Fernández, Lierni; Seoane, Agustín; Buron, Andrea; Bellosillo, Beatriz; Bessa, Xavier; Andreu, Montserrat; Alvarez-Urturi, Cristina
Abstract : INTRODUCTION: Guidelines for surveillance after polypectomy are lacking in strong evidence. Our aim was to identify some precursors of colorectal cancer lesions at 3 years after polypectomy to improve stratification and surveillance programs. METHODS: We included patients with high-risk lesions (HRLs), defined as advanced adenoma (AA), large serrated polyps (SPs), and multiplicity (≥3 of any adenomas/SPs). Data on age, sex, cardiovascular risk factors, pharmacological treatment, and the histological characteristics in each individual, and mutations in genes involved in the most advanced index polyp, were collected. Parameters independently associated with a metachronous HRL diagnosis were evaluated through univariate and multivariate analyses. The results are reported as odds ratios and 95% confidence intervals along with P values. RESULTS: A total of 537 cases (median age: 60.7 years; 66% male) were included. Dyslipidemia and smoking correlated with metachronous HRLs. Multivariate logistic regression analysis showed that the presence of multiplicity with ≥3 polyps on the index colonoscopy was significantly associated with metachronous HRL, AA, proximal AA, and ≥3 polyps at 3 years. In addition, independent predictors of metachronous proximal AA were increasing age, female sex, and the loss of expression of the MLH1 protein. DISCUSSION: Multiplicity was a strong predictor of HRLs at 3 years, although the inclusion of other clinical variables (age, sex, smoking status, and dyslipidemia) improves surveillance recommendations. Without these risk factors, the surveillance could be extended to 5 years; we propose examining the somatic expression of MHL1 in all patients.